PENDEKATAN KONFLIK ORGANISASI TERHADAP MADRASAH EFEKTIF: KERANGKA KONSEPTUAL - Fadhli, Muhammad; Prasetyo, Muhammad Muhammad Anggung Manumanoso (Universitas Islam Negeri Sumatera Utara Medan, 2022)
In a strict and competitive work environment, educational institutions require a strong and supportive organizational base. This research was conducted to find a conceptual framework of reliable organizational conflicts to improve the effectiveness of school organizations. Research methods use library studies by relying on data sourced from a variety of relevant literature, both research journals and books. Data is analyzed by critical analysis of conflicts that occur in Indonesian schools. The results of the study found a conceptual framework of organizational conflicts that mediated the influence of transformational leadership and interpersonal communication on organizational effectiveness. The conceptual framework is expected to be beneficial to organizational managers, educational practitioners, researchers and academics as an effort to revitalize and develop higher competitive organizations. In general the organizational effectiveness studies are concerned with aspects of motivation, leadership and communication, however the originality of the study this time makes organizational conflict a contributing factor for organizational effectiveness.